The association between hair cortisol concentrations and mental disorders in adults with traumatic experiences: a systematic review - Cláudia Vanessa Camacho de Sousa (2022)
Objective: Hair cortisol concentrations (HCC) have been established as a long-term marker of hypothalamic-pituitary-adrenal (HPA) axis activity. In this systematic review, we aimed to investigate the association between HCC and adult mental disorders on patients exposed to traumatic experiences. Methods: This review followed the PRISMA guidelines. Records were identified through PubMed, Web of Science, and PsycInfo databases and were analyzed independently by two investigators. Results: The initial research revealed a total of 353 articles and 30 were included. Traumatic experiences were associated with alterations on the HPA axis, with recent onset traumatic events revealing higher HCC, and traumatic events that happened early in life being associated with lower HCC. In general, depression and bipolar disorder were associated with higher HCC, while posttraumatic stress disorder, schizophrenia, and substance abuse were with lower HCC. The relationship between HCC and anxiety was unclear. Conclusion: Future research should attempt to investigate traumatic events separately from life adversities, since they can influence the HPA axis differently, and should consider examining the potential role of HCC on understanding the pathophysiology, evolution and treatment of mental disorders.